2015
DOI: 10.1016/j.jascer.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Structural and chemical analysis of silica-doped β-TCP ceramic coatings on surgical grade 316L SS for possible biomedical application

Abstract: Please cite this article in press as: K. Prem Ananth, et al., Structural and chemical analysis of silica-doped ␤-TCP ceramic coatings on surgical grade 316L SS for possible biomedical application, J. Asian Ceram. Soc. (2015), http://dx. a b s t r a c tWe have developed a novel approach to introduce silica-doped ␤-tricalcium phosphate (Si-␤-TCP) on 316L SS substrates for enhanced biological properties. Doping of ␤-TCP with silica loadings ranging from 0 to 8 mol% was carried out using chemical precipitation met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…2 and listed in Table I were located at ~594 and ~447 cm -1 , which referred to the Al-O bending vibration of the Al-OH groups. In addition, 640 cm -1 peak represented the stretching vibration of the Al-O band and identified the typical absorption band of α-Al 2 O 3 , ~3300-3510 cm -1 represented the broadening vibration of the O-H bands, and the stretching vibrations of the C-H band were located at ~2866 and ~2924 cm -1 [17][18][19]. Fig.…”
Section: Methodsmentioning
confidence: 91%
“…2 and listed in Table I were located at ~594 and ~447 cm -1 , which referred to the Al-O bending vibration of the Al-OH groups. In addition, 640 cm -1 peak represented the stretching vibration of the Al-O band and identified the typical absorption band of α-Al 2 O 3 , ~3300-3510 cm -1 represented the broadening vibration of the O-H bands, and the stretching vibrations of the C-H band were located at ~2866 and ~2924 cm -1 [17][18][19]. Fig.…”
Section: Methodsmentioning
confidence: 91%
“…It has been suggested that surface chemistry plays an important role in this process even the functional groups of materials have a large effect on the bone bonding property [67]. Negative groups (OH − and PO 4 3− ) are important for the apatite formation [68]. During soaking period, the positive ions include Ca 2+ , Mg 2+ and Na 2+ from SBF are attracted by the surface PO 4 3− ions presented in the sample.…”
Section: Sbf Analysismorphological Observationmentioning
confidence: 99%
“…Ionic substitution in both α and βTCP is currently being investigated. A solid-state reaction, as well as the heat treatment of already precipitated powders, are commonly applied to synthesize these materials [ 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ]. It is worth underlining that there are two main directions in ionic modification of α and βTCP.…”
Section: Ionic Substitutions In Non-apatitic Calcium Phosphatesmentioning
confidence: 99%
“…It is not only magnesium that is being introduced into the βTCP crystal lattice. In the literature, following examples of other ionic modifications can be found: sodium [ 127 , 143 ], potassium [ 128 ], silver [ 135 ], manganese [ 132 ], silicon [ 111 , 133 ], strontium [ 107 , 112 , 113 , 114 ], copper [ 136 ], cobalt [ 137 ], aluminium [ 146 ], iron [ 139 , 140 , 141 ], lantanium [ 131 ], and rare earth elements [ 145 ].…”
Section: Ionic Substitutions In Non-apatitic Calcium Phosphatesmentioning
confidence: 99%